Community Participation in Efforts to Overcome the Difficulties of Proving Domestic Violence Crimes in Indonesia - Handono Sardju Sudarno; Faisal Santiago (Budapest International Research and Critics University, 2022)
There is an assumption that the position of women is lower than that of men or is under the authority and will of men. Such a male-female relationship has been institutionalized within the patriarchal family structure and supported by economic and political institutions and by belief systems, including religious systems, which make such relationships seem natural, morally just and sacred in the view of marriage law in Indonesia, women in such an economic way are placed highly dependent on the man who becomes her husband. Cultural values that justify the subordinate position of women are actually confirmed in legislation, for example the Marriage Law of 1974 which firmly distinguishes the roles and positions between husband and wife. Thelaw is not adequate. Legal aspects, in the form of legal substance (content of law), law enforcement officials (structure of law), as well as legal culture in society (culture of law) turned out to be impartial to the interests of women, especially in matters of violence. The Criminal Code, which is a reference for making legal decisions, is felt to be no longer adequate to cover the various realities of violence that occur in society. Domestic Violence (domestic violence) experienced by a wife is very difficult to come to the fore and be reported, due to the pressure factor from her opponent. It requires an understanding of the involvement of other parties to participate in providing a way out of domestic violence pressure.